Comparative advantage or discrimination? Studying male-female wage differentials using displaced workers - Astrid Kunze; Kenneth R. Troske (Institute for the Study of Labor (IZA), 2007)
In this paper we empirically examine differences in search behavior between men and women. We assess hypotheses regarding duration of search, wages and tenure. The hypotheses are derived from two models: the equilibrium search model with discriminatory firms by Black (1995) and an opportunity cost model that extends the Black model by incorporating age varying reservation wages. We identify effects using data on displaced workers and a differences in differences approach. We find that for men and women the duration of search is equal once we limit our estimation to women with a constant number of children in the household. Furthermore, we find no significant differences in the quality of job match between men and women. Finally, male/female wage differentials are largest among young workers but a significant portion of the difference is accounting for by changes in the number of children in the household. All these results suggest that differences in search behavior and outcomes between men and women are due to differences in nonmarket opportunities rather than to discrimination.
Keywords: 330; Search; displaced workers; discrimination; comparative advantage; Arbeitsuche; Fruchtbarkeit; Lohndifferenzierung; Frauenarbeitslohn; Arbeitsmarktdiskriminierung; USA